Regional thermal patterns in Portugal using satellite images (NOAA AVHRR) - Alcoforado, Maria João; Daveau, Suzanne; Lopes, António; Baumgartner, Michael (Finisterra, 1995)
In this paper two NOAA AVHRR diurnal images (channel 4) are used to determine the required procedures aiming at a future operational analysis system in Portugal. Preprocessing and classification operations are described. Strong correlation between air and surface temperature is verified and rather detailed air temperature patterns can be inferred.